Parental reactions, distress, and sense of coherence after prenatal versus postnatal diagnosis of complex congenital heart disease. (16th November 2019) - Bratt, Ewa-Lena; Järvholm, Stina; Ekman-Joelsson, Britt-Marie; Johannsmeyer, Antje; Carlsson, Sven-Åke; Mattsson, Lars-Åke; Mellander, Mats
Abstract: Introduction: A diagnosis of congenital heart disease (CHD) in offspring triggers psychological distress in parents. Results of previous studies have been inconsistent regarding the psychological impact of a prenatal versus a postnatal diagnosis. The aim of this study was to evaluate the influence of the time of diagnosis on levels of parental distress. Methods: Pregnant women and their partners with a fetus diagnosed with complex CHD, parents of children with postnatally diagnosed CHD, and pregnant women and their partners with uncomplicated pregnancies were invited to participate. Data were collected during pregnancy and 2–6 months after delivery using the Hospital Anxiety and Depression Scale, sense of coherence, life satisfaction, and Dyadic Adjustment Scale. Results: During pregnancy, the prenatal group scored lower sense of coherence compared to controls (p=0.044). Postnatally the prenatal group scored lower on sense of coherence compared to the postnatal group and controls (p=0.001; p=0.001). Postnatally, the prenatal and postnatal groups had higher levels of anxiety compared to controls (p=0.025; p=0.0003). Life satisfaction was lower in the prenatal group compared to that in the postnatal group and in controls (p=0.000; p=0.0004). Conclusion: Parents with a prenatal diagnosis of CHD in offspring report a low sense of coherence already during pregnancy which decreased further at follow-up. The same group reported a lower satisfaction with life compared to parents of a child with postnatal diagnosis of CHD and parents of a healthy child. This motivates further efforts to improve counselling and support during pregnancy and for parents after a prenatal diagnosis.